2021
DOI: 10.3389/fped.2021.661796
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mental Problems for Chinese Children and Adolescents During COVID-19 in China: A Systematic Review and Meta-Analysis

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) has caused mental problems among the public and medical staff in China, especially for children and adolescents, a vulnerable group that might present with more mental problems. It seems that there is a rapid growth in the mental problems (such as depression or anxiety) of Chinese children and adolescents during the outbreak of COVID-19. Although several studies reported the prevalence of depression or anxiety problems for children and adolescents, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 38 publications
1
68
2
Order By: Relevance
“…A total of 24 citations met our preliminary criteria and were retained for full-text review. After full-text evaluation, 17 systematic reviews [29,34,[48][49][50][51][52][53][54][40][41][42][43][44][45][46][47], including 6 meta-analytic reviews [34,42,43,46,49,51] met all criteria of this umbrella review and were selected for further analysis (see Table 2).…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 24 citations met our preliminary criteria and were retained for full-text review. After full-text evaluation, 17 systematic reviews [29,34,[48][49][50][51][52][53][54][40][41][42][43][44][45][46][47], including 6 meta-analytic reviews [34,42,43,46,49,51] met all criteria of this umbrella review and were selected for further analysis (see Table 2).…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
“…The methodological quality of the reviews was assessed using the JBI critical appraisal checklist (See Supplementary Material). Most of the reviews (n = 13) included in this umbrella review were of high quality [29,34,51,53,54,[40][41][42][43][44][48][49][50], whereas the remaining (n = 4) reviews had medium quality [45][46][47]52]. None of the reviews were identified to have low methodological quality as per the JBI checklist.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations